SIMULASI PENGARUH POSISI SALURAN UDARA MASUK DAN KELUAR TERHADAP DISTRIBUSI TEMPERATUR RUANG AC - - Harianto (Universitas Muhammadiyah Semarang, 2009)
The air conditioning room was uncomfortable is probably due to the temperature distribution is notequitable. This is caused due to placement of inlet and outlet is not correct. With the numeric method,numeric calculations can simulate the temperature distribution pattern of the placement position of inletand outlet. The five different types of placement of inlet and outlet had done simulated and produced thebest condition is a second type.